SPIRITUAL WELL BEING IN RURAL WOMEN WHO MARRY LATE IN SUMENEP - Masfufah; Syahrul (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
Spiritual well-being is interconnected with mental health and significantly contributes to health maintenance and recovery from mental illness for all individuals, especially women who marry later in rural regions. The unfavorable perception of rural communities towards individuals who delay marriage manifests in stereotypes such as “old maid,” leading to gossip and labels like unmarketable, selective, playing hard to get, ugly, and very career-oriented. The research aimed to identify the conditions and factors affecting spiritual well-being in rural women who marry later, employing a qualitative phenomenological methodology. Fisher's theory of spiritual well-being was utilized for data analysis, as it offers a comprehensive conceptual framework that accommodates the diverse perspectives articulated in public discourse on spirituality and the viewpoints of historical figures. The study indicates that the spiritual well-being of rural women in Bilapora Rebba Village aligns with four aspects or domains of spiritual well-being, though it does not entirely encompass every element within each domain. The determinants affecting the spiritual well-being of village women who marry later in Bilapora Rebba Village encompass identity, life meaning, forgiveness, respect, kindness, environmental harmony, creator worship, peace with God, prayer practices, self-awareness, and relationships with nature and its wonders.